Law as punishment/law as regulation - Sarat, Austin; Douglas, Lawrence; Umphrey, Martha Merrill (Amherst series in law, jurisprudence, and social thought., 2011)
Law depends on various modes of classification. How an act or a person is classified may be crucial in determining the rights obtained, the procedures employed, and what understandings get attached to the act or person. Critiques of law often reveal how arbitrary its classificatory acts are, but no one doubts their power and consequence. This book considers the problem of law's physical control of persons and the ways in which this control illuminates competing visions of the law: as both a tool of regulation and an instrument of coercion or punishment.